Efficacy and tolerability of using platelet‐rich plasma versus chemical peeling in periorbital hyperpigmentation - Ellabban, Noura F.; Eyada, Moustafa; Nada, Hesham; Kamel, Noha (Journal of cosmetic dermatology, 2019)
Background Various therapeutic modalities for periorbital hyperpigmentation (POH) have been proposed. Objective This study was designed to compare the efficacy and tolerability of autologous platelet‐rich plasma (PRP) and chemical peeling in POH. Subjects and methods Forty‐two patients were enrolled in this study and randomly subdivided into two groups. Group A patients were assigned to receive four sessions of chemical peeling using trichloroacetic acid and lactic acid, while group B was assigned to patients who received four sessions of PRP injection with 2 weeks of intervals. Patients were assessed by digital photographs. The degree of improvement included four degrees from poor to excellent, and side effects were reported. Results Females constituted 38 out of 42 patients (mean age, 28.14 ± 3.47 years). There was a significant improvement in favor of chemical peeling over PRP. Good improvement occurred in 47.6% in the group A versus 4.8% in group B (P < 0.001). None of the PRP group had excellent improvement, while 38% of chemical peeling group did. Most of group A patients reported very pleased (47.6%) to excellent (38%) degree, in contrast to group B where 52.5% were just pleased (P < 0.001). Some of group A patients experienced itching (14.3%) and redness (14.3%), while in group B, they experienced pain (23.8%) and edema (14.3%) with nonsignificant difference between both groups (P = 0.07). Conclusions Both PRP and chemical peeling are effective for treatment of POH; however, chemical peeling is much more effective, tolerable, and satisfying procedure than PRP.